2008
DOI: 10.1002/pbc.21577
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of parental overprotection, perceived vulnerability, and parenting stress to behavioral, emotional, and social adjustment in children with cancer

Abstract: Specific parenting variables appear to be related to specific adjustment outcomes in children with cancer. Longitudinal follow-up of these children is necessary to determine the developmental trajectory of parent variables and long-term child outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
78
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(90 citation statements)
references
References 30 publications
9
78
1
2
Order By: Relevance
“…10 Perceived vulnerability can lead to overprotective behavior in parents and psychological problems in children, such as separation anxiety, psychosomatic complaints, impaired peer relationships and poor school results. 10 In a sample of parents of children with cancer, perceived vulnerability predicted child emotional adaptation (that is, anxiety, depression) 11 and in a sample of parents of children with chronic illnesses, perceived vulnerability predicted illness uncertainty. 12 Perceived vulnerability has not yet been studied in parents of SCT survivors.…”
Section: Introductionmentioning
confidence: 99%
“…10 Perceived vulnerability can lead to overprotective behavior in parents and psychological problems in children, such as separation anxiety, psychosomatic complaints, impaired peer relationships and poor school results. 10 In a sample of parents of children with cancer, perceived vulnerability predicted child emotional adaptation (that is, anxiety, depression) 11 and in a sample of parents of children with chronic illnesses, perceived vulnerability predicted illness uncertainty. 12 Perceived vulnerability has not yet been studied in parents of SCT survivors.…”
Section: Introductionmentioning
confidence: 99%
“…The role of parents and family functioning in relation to child social outcomes is well established (Yeates et al 2007). For example, parental stress is related to child's social adjustment (Colletti et al 2008). Families who are coping better with the disorder may have more opportunity for family social outings, and children therefore have more social experiences.…”
Section: Discussionmentioning
confidence: 98%
“…Parental stress affects glycaemic control in children with type I diabetes mellitus (Tsiouli et al 2013) and behaviour and social development in children with cancer (Colletti et al 2008;Hilliard et al 2011) and with spina bifida (Friedman et al 2004). Parents of children with PKU reported their families were less cohesive and adaptive compared with parents of healthy children (Kazak et al 1988), yet no differences were found in GSD I (Storch et al 2008).…”
mentioning
confidence: 94%
“…Majnemer et al [17] also found that higher levels of parental stress were associated with lower psychosocial well-being in their child. Furthermore, parental stress and parental psychopathology were also associated with poorer child-reported behavioral and social Data are presented as mean (standard deviation) GHQ-28 a higher score indicates worse General Health, SSE a higher score indicates more social support a Significantly different from norm females, p \ 0.05 adjustment [4] and both physical and psychosocial HRQoL [36] in pediatric cancer survivors. In our study, parental moderators did not predict changes in physical HRQoL subscales.…”
Section: Discussionmentioning
confidence: 99%